Analisis Persediaan Pesanan Telur pada Agen Telur SNM Menggunakan Metode Economic Order Quantity (EOQ) - Nisa, Natasya Khairun; Nugroho, Septio Catur; Batubara, Adila Hafizah; Gustina, Putri Nadira; Afifah, Arifinaya Siti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Chicken egg production in Indonesia continues to increase, and inventory control is important to maintain distribution stability and anticipate demand fluctuations. The purpose of the study was to analyze the inventory control of chicken eggs at SNM Egg Agent using the Economic Order Quantity (EOQ) method. This approach allows systematic and measurable calculations to determine optimal inventory efficiency. The results of calculations using the EOQ method are 709 kg, ROP is 549 kg, and the ideal order frequency is 102 times per year with a calculation of the time distance between orders of 240 days. By applying EOQ, agents can save inventory costs of Rp12,936,303 compared to the actual method.